Research Capacity Strengthening in Sub-Saharan Africa: Recognizing the Importance of Local Partnerships in Designing and Disseminating HIV Implementation Science to Reach the 90–90–90 Goals. - Kalbarczyk, Anna; Davis, Wendy; Kalibala, Sam; Geibel, Scott; Yansaneh, Aisha; Martin, Nina A.; Weiss, Ellen; Kerrigan, Deanna; Manabe, Yukari C. (AIDS & Behavior)
Capacity building in implementation science is integral to PEPFAR's mission and to meeting the 90–90–90 goals. The USAID funded Project SOAR sponsored a 4 day workshop for investigators and governmental and non-governmental partners from 12 African countries. The workshop was designed to address both findings from a pre-workshop online needs assessment as well as capacity challenges across the capacity building pyramid, from individual skills to institutional systems and resources. Activities were output-oriented and skill based. An online survey evaluated sessions and changes in perceptions of needs; a majority of respondents strongly agreed that after the workshop, they better understood their personal and institutional capacity strengthening needs. Participants 'strongly agreed' that workshop content was relevant to their jobs (90%) and that they left the workshop with a specific plan for conducting future research (65%). Workshop results suggest that skill-building should be done in conjunction with systems capacity building within the cultural context.